Lubiprostone: evaluation of the newest medication for the treatment of adult women with constipation-predominant irritable bowel syndrome - Tisha N Lunsford; Lucinda A Harris (Dove Medical Press, 2010)
Tisha N Lunsford, Lucinda A HarrisDepartment of Gastroenterology and Hepatology, Mayo Clinic – School of Medicine, Scottsdale, Arizona, USAAbstract: Irritable bowel syndrome (IBS) is a chronic disorder that affects primarily female patients and is thought also to afflict approximately 7%–10% of the population of the Western World. Although bowel habits may change over the course of years, patients with IBS are characterized according to their predominant bowel habit, constipation (IBS-C), diarrhea (IBS-D), or mixed type (IBS-M), and treatments are focused toward the predominant symptom. Current treatments for IBS-C have included fiber, antispasmodics, osmotic and stimulant laxatives, and the now severely limited 5-HT4 agonist tegaserod. No one agent has been universally successful in the treatment of this bothersome syndrome and the search for new agents continues. Lubiprostone (Amitiza®), a novel compound, is a member of a new class of agents called prostones and was approved for the treatment of chronic idiopathic constipation in 2006 at a dose of 24 µg twice daily and then in 2008 for the treatment of IBS-C in women only at a dose of 8 µg twice daily. Its purported mechanism is as a type 2 chloride channel activator, but recent evidence suggests that it may also work at the cystic fibrosis transport receptor. This article will compare the newly proposed mechanism of action of this compound to the purported mechanism and review the structure, pharmacology, safety, efficacy, and tolerability of this new therapeutic option. Clinical trial data leading to the approval of this agent for the treatment of IBS-C and the gender-based understanding of IBS, as well as this agent’s place among existing and emerging therapies, will be examined.Keywords: large intestine, functional bowel disorder, therapy